Pengaruh Media Terbuka dan Tertutup terhadap Kadar Asam Lemak Bebas pada Kondisi Suhu Kamar - Lestari, Destriani Umi; Wicaksono, Dimas Aji (Lembaga Yasin AlSys, 2024)
Free fatty acids (ALB) are fatty acids that exist in a free state and are no longer related to glycerol. The method used in ALB analysis in CPO uses the alkalimetric titration method with the principle of determining acid levels using a standard alkaline solution that has known the exact concentration. The data collection process is carried out by calculating the % ALB in open and closed media CPO which is then calculated in excel to find out the comparison of the increase in % ALB so that the graph is obtained. a significant increase occurs in open media CPO because open media is more rapidly oxidized and more susceptible to contamination by air so that there is a faster increase in open media samples so that in open media the smell is more rancid than closed media due to the result of oxidation, namely hydroperoxide which gives a rancid smell and gives a brownish color to CPO.